2009
DOI: 10.1148/radiol.2523081676
|View full text |Cite
|
Sign up to set email alerts
|

Small Hepatocellular Carcinoma: Is Radiofrequency Ablation Combined with Transcatheter Arterial Chemoembolization More Effective than Radiofrequency Ablation Alone for Treatment?

Abstract: Combined radiofrequency ablation plus TACE and radiofrequency ablation alone have equivalent effectiveness for the treatment of small (< or =3 cm) HCCs, so the combination treatment may not be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
159
3
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(184 citation statements)
references
References 33 publications
4
159
3
3
Order By: Relevance
“…control even when lesions occur on the surface of the liver or near blood vessels. Multiple studies have been conducted on RFA/TACE, and a systematic review (23) performed a meta-analysis of eight clinical trials (24)(25)(26)(27)(28)(29)(30). However, the majority of these studies examined HCC tumors >3 cm in diameter, and only one examined small HCCs (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…control even when lesions occur on the surface of the liver or near blood vessels. Multiple studies have been conducted on RFA/TACE, and a systematic review (23) performed a meta-analysis of eight clinical trials (24)(25)(26)(27)(28)(29)(30). However, the majority of these studies examined HCC tumors >3 cm in diameter, and only one examined small HCCs (28).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have been conducted on RFA/TACE, and a systematic review (23) performed a meta-analysis of eight clinical trials (24)(25)(26)(27)(28)(29)(30). However, the majority of these studies examined HCC tumors >3 cm in diameter, and only one examined small HCCs (28). The meta-analysis revealed that rate of local tumor progression, OS, local progression-free survival and event-free survival were not significantly different between the combination therapy and RFA alone.…”
Section: Discussionmentioning
confidence: 99%
“…After stratification for tumor number and size, neither 1-, 3-, and 5-year tumor progression rates nor overall survival significantly differed between the single-tumor group and multi-tumor group. It seems relevant that the two randomized trials reported (39,40) failed to demonstrate a statistically significant advantage for the TACE plus RFA combination versus RFA alone in a cohort of small and intermediate-sized HCCs. As a matter of fact, Morimoto and colleagues demonstrated that such a combination therapy is safe and effective for extending the ablated area, thereby contributing to restricting local tumor progression, but a larger number of patients may be needed to confirm the survival benefits (40).…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, Shibata and colleagues reported their experience in a prospective randomized trial comparing TACE plus RFA versus RFA alone in patients fulfilling the following inclusion criteria: three or fewer HCC nodules 3 cm in diameter or smaller, CTP class A or B cirrhosis, no imaging evidence of tumor invasion into the major portal or hepatic vein branches, no extrahepatic metastasis, and a platelet count of more than 40,000 cells/mm 3 (39). A total of 89 patients entered the study, 46 in the combined therapy group and 43 in that for RFA alone.…”
Section: Ablative Therapies: Radiofrequency Ablation (Rfa) -Percutanementioning
confidence: 99%
“…Accordingly the debate arises on to what is the best option for these patients: immediate ablation or wait until the tumor grows and then patients afford exception points and have real options of attracting an organ [71] . Several studies have shown the efficacy of local therapies on very early HCC [72][73][74][75][76] . Sala et al [77] reported a 50% survival at 5 years in Child A patients and treatment response in 70% of nodules < 3 cm and 50% in nodules rence out of transplantable criteria and then loose the opportunity for LT. N'Kontchou et al [79] reported promising results with the "two step" strategy, using RFA as first line treatment in patients eligible for LT.…”
Section: Local Therapiesmentioning
confidence: 99%